Analisis Terhadap Pelemahan Hak-Hak Pekerja Dalam Omnibus Law UU Cipta Kerja Perspektif Critical Legal Studies - Afifah, Rosalina; Syahrial, Andra Agil; Imawan, Moh. Dafiz (Media Hukum Indonesia (MHI), 2024)
Law Number 11 of 2020 concerning Job Creation which uses the omnibus law method has sparked widespread controversy, especially in the employment aspect. Significant changes to several previous legal provisions are considered to weaken the protection of workers' rights. The research method used is normative juridical with a statutory approach which refers to Law Number 11 of 2020 concerning Job Creation. This research analyzes this issue from a Critical Legal Studies perspective, which highlights law as a social construction influenced by the interests of economic and political elites. The research results show that the Job Creation Law is not completely neutral and objective. On the contrary, this law strengthens the dominance of employers' interests at the expense of workers' basic rights. This article emphasizes the need for revision of the Job Creation Law to create a balance between investment interests and protecting workers' rights. By involving the active participation of all stakeholders, more inclusive and socially just regulations can be realized.